Students' Perceptions on English Learning Materials: Need Analysis of Islamic Studies Students - Zaitun Warda; Ahmad Amin Dalimunte (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2022)
The English material has not met the needs of students and was created with the lecturer in mind. This study analyzes the English language needs of students majoring in Islam (ushuluddin) at the State Islamic University of North Sumatera, Indonesia. This study applied a qualitative descriptive research method to explore student perspectives on ESP courses. The research data was obtained through interviews and data collection of material documentation. The findings in this study proved that students who learned ESP need good material and can apply the results at the end of the lesson. Besides, what they have learned so far was the obtained course in high school, so it was not so difficult to understand. Hence, the language skills they command must be fulfilled from listening, speaking, reading, and writing to support their insights with Islamic foundations and majors. In sum, the materials of ESP should be formulated by practitioners of English for Specific Purposes (ESP) who know ESP instruction, and the aim of ESP might concern the improvements in students' proficiency in English. Thus, the students are better academically and professionally in the work domain.